2022
DOI: 10.1136/jnnp-2021-328738
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of deep brain stimulation for treatment-resistant obsessive-compulsive disorder: systematic review and meta-analysis

Abstract: Deep brain stimulation (DBS) is an established and growing intervention for treatment-resistant obsessive-compulsive disorder (TROCD). We assessed current evidence on the efficacy of DBS in alleviating OCD and comorbid depressive symptoms including newly available evidence from recent trials and a deeper risk of bias analysis than previously available. PubMed and EMBASE databases were systematically queried using Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines. We included studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…The neural basis for OCD, a disabling psychiatric condition with a lifetime prevalence of 2–3%, is uncertain ( Gadot et al, 2022 ). The classical neurobiological models of OCD based primarily on dysfunctional parallel cortico-striatal loops have been questioned, while the precise role of other implicated brain regions, such as amygdala and cerebellum, also remains unclear ( Kammen et al, 2022 ).…”
Section: Updates From Asiamentioning
confidence: 99%
“…The neural basis for OCD, a disabling psychiatric condition with a lifetime prevalence of 2–3%, is uncertain ( Gadot et al, 2022 ). The classical neurobiological models of OCD based primarily on dysfunctional parallel cortico-striatal loops have been questioned, while the precise role of other implicated brain regions, such as amygdala and cerebellum, also remains unclear ( Kammen et al, 2022 ).…”
Section: Updates From Asiamentioning
confidence: 99%
“…37 Moreover, in a recent meta-analysis, DBS of these and other regions resulted in a 47% reduction in Yale-Brown Obsessive-Compulsive Scale scores, similar to ablative procedures for OCD. 38 It is worth emphasizing that until more prospective, blinded placebocontrolled trials for people with severe, refractory OCD are conducted, the procedure may continue to be underutilized and inaccessible to those most in need. A recent work addressing the need for improved access was discussed by Davis et al, who suggested that restriction of DBS for OCD by insurers on the basis of being investigational is both unethical and illegal.…”
Section: Deep Brain Stimulation and Modern Usesmentioning
confidence: 99%
“…A significant impediment to progress has been the lack of reliable neural biomarkers for psychiatric disease, although several groups have recently identified potential electrochemical and electrophysiological markers. 38,39 Local field potential data collection (e.g., using scalp electroencephalography [EEG], stereo-EEG, magnetoencephalography, and electrocorticography) is one of the most active areas of research, in particular, investigations assessing changes related to internal emotional states. 37 Artificial intelligence algorithms are increasingly being used to process these vast amounts of information.…”
Section: Future Directionsmentioning
confidence: 99%
“…Patients with treatment-refractory OCD may be appropriate candidates for DBS. As the JNNP article by Gadot et al 4 highlights, there have been multiple trials of DBS for treatment-refractory OCD, the outcomes of DBS are quite positive and adverse events quite uncommon. In fact, the Gadot et al article further refines our knowledge of the optimal target for electrode placement.…”
mentioning
confidence: 99%
“…Without such coverage (and less than 40% of eligible patients have received coverage for DBS from their insurance companies),5 DBS is prohibitively expensive for the majority of individuals. One hopes that a detailed and scientifically balanced study such as the one by Gadot et al 4 may ultimately make an impact in terms of increasing the number of people with treatment- refractory OCD who will receive DBS and provide much needed data to insurance companies so that they will cover the procedure.…”
mentioning
confidence: 99%